2019
DOI: 10.1002/ece3.5844
|View full text |Cite
|
Sign up to set email alerts
|

Desert‐like badlands and surrounding (semi‐)dry grasslands of Central Germany promote small‐scale phenotypic and genetic differentiation inThymus praecox

Abstract: Environmental heterogeneity among sites can generate phenotypic and genetic variation facilitating differentiation and microevolution of plant populations. Badlands are desert‐like, predominantly vegetation‐poor habitats often embedded in (semi‐)dry grasslands. The desert‐like conditions of badlands demand extreme adaptation of plants, that is, phenotypic modifications in short‐term and/or natural adaptation in long‐term. However, detailed knowledge is missing about both plant phenotypic and genetic differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 148 publications
(235 reference statements)
3
18
0
Order By: Relevance
“…Intraspecific functional trait variation captured by iFD CV is probably the response of populations to increased abiotic and biotic environmental differences within their habitats (see also Ghalambor et al, 2007; Nicotra et al, 2010, 2015): as shown, iFD CV was positively correlated to within‐habitat heterogeneity, suggesting that the more environmentally variable a habitat, the higher the intraspecific functional trait variation in T. montanum populations. Results are line with literature showing associations between functional trait values and diversity, and environmental conditions within and across species (e.g., Albert et al, 2010; Bernhardt‐Römermann, Gray, et al, 2011; Bucher et al, 2016; Díaz & Cabido, 2001; Gratani, 2014; Karbstein et al, 2019; König et al, 2018; Violle et al, 2007). Intraspecific functional differences are known to facilitate a more flexible response to varying abiotic conditions (see, e.g., Bucher et al, 2016 for elevational gradients; Karbstein et al, 2019 for small‐scale habitat differences).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Intraspecific functional trait variation captured by iFD CV is probably the response of populations to increased abiotic and biotic environmental differences within their habitats (see also Ghalambor et al, 2007; Nicotra et al, 2010, 2015): as shown, iFD CV was positively correlated to within‐habitat heterogeneity, suggesting that the more environmentally variable a habitat, the higher the intraspecific functional trait variation in T. montanum populations. Results are line with literature showing associations between functional trait values and diversity, and environmental conditions within and across species (e.g., Albert et al, 2010; Bernhardt‐Römermann, Gray, et al, 2011; Bucher et al, 2016; Díaz & Cabido, 2001; Gratani, 2014; Karbstein et al, 2019; König et al, 2018; Violle et al, 2007). Intraspecific functional differences are known to facilitate a more flexible response to varying abiotic conditions (see, e.g., Bucher et al, 2016 for elevational gradients; Karbstein et al, 2019 for small‐scale habitat differences).…”
Section: Discussionsupporting
confidence: 90%
“…Results are line with literature showing associations between functional trait values and diversity, and environmental conditions within and across species (e.g., Albert et al, 2010; Bernhardt‐Römermann, Gray, et al, 2011; Bucher et al, 2016; Díaz & Cabido, 2001; Gratani, 2014; Karbstein et al, 2019; König et al, 2018; Violle et al, 2007). Intraspecific functional differences are known to facilitate a more flexible response to varying abiotic conditions (see, e.g., Bucher et al, 2016 for elevational gradients; Karbstein et al, 2019 for small‐scale habitat differences). Thus, iFD CV likely affects population growth and reproduction with positive consequences for survival and fitness (see also Nock et al, 2016; Violle et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There are few publications on this taxon in the literature. They concern cytological, genetic and biochemical issues, some of its subspecies (Trela-Sawicka, 1972;Mártonfi and Mártonfiová, 1996;Avci, 2011;Karbstein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%